Pengaruh Elisitasi dengan Verticillium dahliae Kleb dan Rhizoctonia Solani Kuhn terhadap kandungan Gosipol dalam kalus Gossypium hirsutum L pada beberapa tingkat Subkultur - Suci Rahayu; Rizkita Rachmi Esyanti; Arbayah H Siregar (Fakultas Biologi | Universitas Jenderal Soedirman, 2006)
An experiment on gossypol content hasbeen conducted on callus derived from Gossypium hirsutum L. subcultures 5, 6, and 7 after elicitation with Verticillium dahliae Kleb and Rhizoctonia solani Kuhn. Callus was cultured on solid Linsmaier and Skoog (LS) medium supplemented with 10 –5 M NAA and 10 –6 M 2,4-D, and subcultured for 5, 6, and 7 times. Callus was then elicited with 40 μg dry weight /ml homogenate of fungi derived from V. dahliae and R. solani, and harvested 0, 2, 4, and 6 days after elicitation. The gossypol was analyzed qualitatively and quantitatively using High Performance Liquid Chromatography (HPLC). The maximum gossypol content elicited with R. solani was obtained on callus subculture 5, which was harvested on 4 days after elicitation, i.e. 177,995 ± 0,248 μg/g dry weight, whilst that with V. dahliae was obtained on subculture 5, harvested four days after elicitation, i.e.108,021± 0,507 μg/g dry weight. The gossypol content of control callus on subculture 5, 6, and 7 was 37,885 ± 0,779 μg/g dry weight 23,170 ± 0,003 μg/g dry weight, 12,284 ± 0,221 μg/g dry weight, respectively. The subculture level, elicitor type, and harvesting time gave significant effect on gossypol content of G. hirsutum callus culture.